A Practical Guide to Concentrated Insulin for Pharmacists. (October 2014) - Andres, Jennifer; Clements, Jennifer N.
Purpose: Insulin improves glycemic control in several ways, for example, by stimulating glucose uptake in the muscle and inhibiting hepatic glucose production. It has other mechanisms of action for correcting the abnormal metabolism of proteins, fats, and carbohydrates. The formulation of concentrated insulin (U-500) is a higher potency of insulin than the U-100 regular formulation. It is indicated for children and adults with type 1 and type 2 diabetes who have not achieved adequate glycemic control with exercise and proper dietary habits. However, the unique characteristics of concentrated insulin require that a patient be educated on its use. This article provides a practical guide for pharmacists on the use of concentrated insulin in both inpatient and outpatient settings and highlights specific concerns and management strategies. Conclusion: Concentrated insulin works in the same mechanism as U-100 insulin formulations for treating type 1 and type 2 diabetes. Pharmacists are knowledgeable about managing the disease and can identify patients who will benefit with treatment of concentrated insulin. They can provide recommendations to prevent and resolve situations, such as dosing errors, which arise in patients on concentrated insulin and can educate patients and health care professionals on dosing conversions and titration.